Platelets and platelet-derived extracellular vesicles: their role in lung cancer dissemination and premetastatic niche formation - Locatelli, Camilla; Ferrario, Nicole; Fortunato, Orazio; Ghidotti, Patrizia; Crescitelli, Rossella (Frontiers in Immunology, 2025)
Metastasis, the primary cause of cancer-related mortality, is sustained by complex interactions between tumor cells and host-derived factors. Extracellular vesicles, membrane-bound particles that mediate intercellular communication, have emerged as critical regulators of this process. Among them, platelet-derived extracellular vesicles represent the most abundant EV population in circulation and extend the multifaceted influence of platelets in cancer progression. Platelets actively contribute to metastasis by shielding circulating tumor cells from immune surveillance, promoting vascular remodelling, facilitating extravasation, and releasing soluble factors that shape the premetastatic niche. Platelet-derived extracellular vesicles further potentiate these processes by delivering a heterogeneous cargo of proteins, nucleic acids, and lipids to endothelial, stromal, and immune cells, thereby promoting angiogenesis, extracellular matrix remodelling, immune suppression, and organ-specific metastatic colonization. This review summarizes current evidence on the cooperative roles of platelets and platelet-derived extracellular vesicles in metastatic dissemination, with particular emphasis on their contribution to lung premetastatic niche formation and their emerging translational potential in oncology.